Environmental education, social justice and teacher education: Enabling meaningful environmental learning in local contexts - Reddy, C. (South African Journal of Higher Education, 2021)
Short (2010, 7) indicates that continued global population growth, technological advancement and subsequent burdens on the natural world from consumer demands during the 20th century has led to many environmental issues and concerns. According to (Edwards 2011) the resultant or consequent problems in the environment could reach levels that could push the planet to levels of ecological disaster. Evidence of ecosystem destruction, human induced climate change, social injustice and increasing economic strife is mounting in many parts of the world. Environmental Education (EE) has often been mentioned as an important response to the issues mentioned above, but if EE is to contribute to the transformation to sustainable living, teachers have a vital role to play. Thus, teacher education programmes need to prepare preservice adequately for these challenges arising in the 21st century. This exploratory theoretical article reviews approaches and ideas for the development of curriculum for environment related education in teacher education programmes. I draw on the work of Short (2002) related to place based collaborative knowledge production and Jickling and Wals (2008), active and co-operative learning in context, to inform curriculum development possibilities for EE. The research highlights the importance of active participation for meaningful environmental learning and presents arguments for including local environmental issues and knowledge development during the practicum as key activities to enable meaningful environmental learning and social justice in teacher education programmes.